Atypical RNAs in the coelacanth transcriptome. Issue 6 (30th October 2013) - Nitsche, Anne; Doose, Gero; Tafer, Hakim; Robinson, Mark; Saha, Nil Ratan; Gerdol, Marco; Canapa, Adriana; Hoffmann, Steve; Amemiya, Chris T.; Stadler, Peter F.; Amemiya, Chris; Meyer, Axel
ABSTRACT Circular and apparently trans‐spliced RNAs have recently been reported as abundant types of transcripts in mammalian transcriptome data. Both types of non‐colinear RNAs are also abundant in RNA‐seq of different tissue from both the African and the Indonesian coelacanth. We observe more than 8, 000 lincRNAs with normal gene structure and several thousands of circularized and trans‐spliced products, showing that such atypical RNAs form a substantial contribution to the transcriptome. Surprisingly, the majority of the circularizing and trans‐connecting splice junctions are unique to atypical forms, that is, are not used in normal isoforms. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 342–351, 2014. © 2013 Wiley Periodicals, Inc.